Media barometer 2005 - Nordicom - Nordic Information Centre for Media and Communication Research, University of Gothenburg (University of Gothenburg, 2008)
The first Media Barometer was conducted in 1979 and since then the survey has been carried out annually. The study intends to highlight the proportion of the Swedish population having used on an average day in each year studied a number of specific media: radio, television, teletext, video, movies, audio cassette, record player / CD, newspaper, tabloid, weekly / monthly newspaper, magazine and book (from 1995 are also direct mail and new media technologies are included); a specific area is related to Internet use.

Purpose:

Describe the trends and changes in people's use of mass media.

Mediebarometern genomfördes första gången 1979 och har sedan dess genomförts varje år. Studien avser att belysa hur stor andel av den svenska befolkningen som en genomsnittlig dag under respektive år tagit del av ett antal enskilda medier: radio, TV, text-TV, video, bio, ljudkassett, grammofon/CD, morgontidning, kvällstidning, vecko-/månadstidning, tidskrift och bok (från 1995 omfattas även direktreklam och ny medieteknologi); ett särskilt område rör internetanvändning.

Syfte:

Beskriva tendenser och förändringar i människors nyttjande av massmedier.
Mediebarometern 2005
Keywords: mass media; massmedia; mass media exposure; massmediaexponering; newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; cinema attendance; biobesök; music; musik; newspaper press; nyhetspress; book use; bokanvändning; local broadcasting; lokalsändningar; radio news; radionyheter; radio stations; radiostationer; satellite television; satellit-tv; television channels; tv-kanaler; cable television; kabel-tv; television advertising; tv-reklam; television news; tv-nyheter; television programmes; tv-program; local press; lokalpress; internet; internet; internet access; internetåtkomst; electronic mail; elektronisk post; audio and video equipment; ljud- och videoutrustning; information retrieval; informationssökning; teletext; text-tv; mobile communication; mobilkommunikation; access to information and communications technology; tillgång till informations- och kommunikationsteknologi; households; hushåll; reading (activity); läsande; Media; Media; Information society; Informationssamhället; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap